Gregorčičeva poezija danes - Bernik, France (Slavistična revija, 2006)
The author connects the question of the presen-day significance of Gregorčič's poetry with the reception of the poet's work in his time, i.e., the second half of the 19th c. Working towards the present, he stops in the area after World War II, in the 1950s and 1960s. Finally, he attempts to define the value of Gregorčič's poetry from the point of view of a contemporary reader with literary expetise and thematically define the poetical complexes that resounding today, this interpretation does not overlook the musicality of Gregorčič's verse, which is ab easily noticeable, but the least concrete pecularity of his poetry
Keywords: 19. st.; 19th century; domoljubna poezija; duhovniki; eroticism; erotična poezija; Gregorčič, Simon, 1844-1906; patriotism; priests; Slovene literature; Slovene poetry; slovenska književnost; slovenska poezija